Brand Image dan Kepuasan Pelanggan untuk Meningkatkan Loyalitas Konsumen Produk Wardah: Brand Image and Customer Satisfaction to Enhance Consumer Loyalty for Wardah Products - Triyana; Marhamah, Nur Hadianti; Pransisca, Siti Rhinka; Noviyanti, Indah (Universitas Muhammadiyah Luwuk Banggai, 2025)
This study examines the influence of brand image and customer satisfaction on competitive advantage in the context of the Wardah cosmetic brand. In the competitive beauty industry, brand perception and customer experience are crucial in fostering loyalty and market advantage. A quantitative approach was employed, collecting data from 123 respondents, the majority of whom were female. Analysis using SmartPLS indicates that both brand image and customer satisfaction significantly impact product competitive advantage, with customer satisfaction exerting a stronger influence. These results underscore the practical importance of maintaining high service quality and consistent brand communication to strengthen consumer loyalty and long-term competitiveness.